TRADITIONAL PRACTICES OF CAUCASIAN UPBRINGING OF MEN: THE VALUE CONTEXT OF THEIR MODERN EXISTENCE - Akieva, Petimat Hasoltovna (History, Archeology and Ethnography of the Caucasus, 2025)
The spiritual and moral education of young people based on traditional values ​​today determines the main vector of state policy. In strategic documents, the protection of traditional values ​​is designated as an “urgent necessity.” Finding their original manifestation in the spiritual sphere, today traditional values ​​form a single cultural space of a multinational country. The protection of traditional values ​​from compromise by other cultures actualizes the topic of educational and historical heritage as the most important resource. In this connection, the topic of the cultural and educational potential of folklore, including the Nart epic, only increases its relevance. Scientific interest appears in the sphere of discussion of the problem of meaningfulness in modern Caucasian life of moral guidelines reflected in the Nart epic and national models of education. The research methodology was based on the principles of dialectical understanding of the reproduction of traditional values ​​within the framework of socialization and individualization of the individual. The axiological approach made it possible to determine the moral dominants of what should be, the mechanisms for transferring value experience and behavioral models of exemplary. Currently, the traditions of education, as well as the very content of moral and value guidelines, passed down for centuries from generation to generation, are being eroded. While maintaining fidelity to traditional family values, generational and gender hierarchy, and the practice of following the moral assessment of society, modern realities illustrate a change in value orientations among young people: the ambitions and personal affirmation of young people are no longer subordinated to the principles of the common good. The trend towards self-realization based on the principle of individual benefit against the backdrop of shattered mechanisms of “appointment” of role models by society leads to a gradual loss of continuity in traditional upbringing.
Keywords: education; values; nart; respect; harmony; responsibility; modernity